Novel Treatment Technologies for Nutrients Recovery and Biosolids Management - Guo, Hui (My University, 2021)
High energy consumption in conventional wastewater treatment contributes to a large amount of greenhouse emissions and causes environmental problems such as acid rain and climate change. Many technologies, microbial electrolysis cells (MECs), electrodialysis (ED), and anaerobic digestion (AD), were developed to make wastewater treatment more efficient and economical. This thesis investigated novel MECs and ED to decrease energy consumption in wastewater treatment and recover resources from wastewater. In addition, inhibition of ammonia and acetic acid on high-solid AD was examined in this research. The multi-electrode stack design was applied in MECs to treat municipal wastewater. Rapid organic removal and minimized biosolids production were observed in the stacked MECs. In addition to municipal wastewater treatment, MECs can also recover/remove heavy metals from industrial wastewater. Various removal/recovery mechanisms of toxic heavy metals were discussed in this thesis. ED with bipolar membranes (BPMs) was examined to produce high-purity ammonium sulfate from real wastewater steams. This examination indicates valuable nutrients resources (e.g., ammonium sulfate) can be recovered from wastewater and used as land fertilizers for food production. Membrane scaling problems were also evaluated in ED systems since the formation of inorganic scalants can affect the efficiency of nutrients recovery significantly. In addition, the inhibition of ammonia and acetic acid on AD performance was incorporated in a modified anaerobic digestion model (ADM) for reliable simulation of individual biological reactions in high-solid AD. This research contributes to the body of knowledge by developing wastewater treatment technologies with less energy consumption and biosolids production. The reduction of energy consumption and biosolids production can reduce fossil fuel combustion and waste disposal. Resources, such as ammonia and heavy metals, can be recovered and reused by using the investigatory technologies. Therefore, with these developed technologies, wastewater treatment meets the goal of sustainable development and helps to establish a new green circular economy.
Keywords: Nutrients Recovery; Biosolids Management